IMPLEMENTASI IZIN PEMANFAATAN TANAH KAS DESA BERDASARKAN PERATURAN DESA NOMOR 4 TAHUN 2019 KALURAHAN SARIHARJO NGAGLIK - Galih Wicaksana; Ishviati Joenaini Koenti; Takariadinda Diana Ethika (Kajian Hukum, 2022)
Sariharjo Village is a village located in the Special Region of Yogyakarta Province, which is in Sleman Regency and is included in the Kapanewon Ngaglik region, which is geographically located between urban and rural areas, which is very supportive in the trade and other business sectors, besides that there are hotels and other businesses. Existing businesses make the village develop quickly, one of which is the Village Treasury Land as the location that business actors are aiming for because they do not own land in the area. This study aims to analyze the implementation of legal products, namely the Implementation of Village Regulation Number 4 of 2019. Implementation of Village Regulation No. 4 of 2019 concerning Utilization of Sariharjo Village Land, the Village Treasury Land utilization permit has been implemented but implementation in the field is still not optimal. Meanwhile, the role of the Village Government in the Permit Process for Utilization of Village Treasury Land is as a verifier, determining the amount of rent, and as a supervisor.